2002
DOI: 10.1002/1521-396x(200208)192:2<394::aid-pssa394>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural Defects and Relation with Optoelectronic Properties in Highly Mg-Doped GaN

Abstract: A transmission electron microscopy of pyramidal inversion domains induced by Mg doping in MOVPE and bulk GaN is presented. Based on high resolution observations and EDX analysis, two atomic models are proposed for the Mg-rich (0001) inversion domain boundaries. These structural defects appearing for Mg concentrations in the 10 19 cm --3 range are shown to be possible origins for the auto-compensation and the blue luminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
3
26
1
Order By: Relevance
“…Unfortunately, as the Mg concentration in the films is increased the concentration of holes eventually saturates and declines. [2][3][4][5] The origin of this phenomenon is not well understood at present. Doping limiting mechanisms involving the formation of bulk Mg 3 N 2 precipitates 6,7 or compensation by point defects and complexes have been discussed in the literature 3,4,6 but a definitive resolution of the issue has not been achieved.…”
Section: Magnesium Incorporation At "0001… Inversion Domain Boundariementioning
confidence: 58%
See 3 more Smart Citations
“…Unfortunately, as the Mg concentration in the films is increased the concentration of holes eventually saturates and declines. [2][3][4][5] The origin of this phenomenon is not well understood at present. Doping limiting mechanisms involving the formation of bulk Mg 3 N 2 precipitates 6,7 or compensation by point defects and complexes have been discussed in the literature 3,4,6 but a definitive resolution of the issue has not been achieved.…”
Section: Magnesium Incorporation At "0001… Inversion Domain Boundariementioning
confidence: 58%
“…5 These authors performed high-resolution electron microscopy and energy dispersive x-ray spectrometry ͑EDX͒ experiments for Mg-doped GaN films grown by MOVPE, and observed that the films contained pyramidal defects when the Mg concentration exceeded 10 19 /cm 3 . From their EDX studies it was concluded that Mg is present on the ͑0001͒ portion of the pyramidal defect boundary.…”
Section: Magnesium Incorporation At "0001… Inversion Domain Boundariementioning
confidence: 99%
See 2 more Smart Citations
“…According to calculations by Northrup [19] our model would be energetically less favorable, but Mg could be 4-fold coordinated surrounded by 6-coordinated N and it would include change of stacking sequence from ab to bc and a shift on the pyramid side of 0.6 ±0.2Å between Ga sublattices in the matrix and the defect. Romano [20] suggested that the Ga sublattice continues across the pyramid side and Leroux [21] considered that the N sublattice continues across the same boundary, as similarly proposed by Northrup [19]. We believe that only our method gives enough resolution to see particular sublattices which was not presented by any other author up to now.…”
Section: Models and Results Discussionmentioning
confidence: 99%